Citrus flavonoid supplement enhances glycemic and metabolic control in prediabetic patients on metformin: a randomized controlled trial - Cesar, Thais; Oliveira, Maria Rita; Sandrim, Valeria; Mendes, Adriana; Bruder, Ricardo; Oliveira, Rogerio; Sivieri, Katia; Milenkovic, Dragan (Frontiers in Nutrition, 2025)
Background and objectiveCombining natural compounds with conventional drugs is an emerging strategy to improve the management of type 2 diabetes and its precursor, prediabetes. While metformin effectively lowers blood glucose and improves insulin sensitivity, it may cause side effects or lose efficacy over time. Natural agents, particularly polyphenols, are being explored as adjunct therapies to enhance glycemic control, mitigate adverse effects, and slow disease progression. This study evaluated the efficacy of a citrus bioflavonoid-based nutraceutical as an adjunct to metformin therapy in prediabetic individuals, with a focus on metabolic, inflammatory, oxidative, hormonal, and nutritional-clinical outcomes.MethodsIn this 12-week randomized, double-blind, placebo-controlled trial, participants received either metformin plus the citrus flavonoid supplement (250 mg/day) or metformin plus placebo.ResultsAt the end of the intervention, the nutraceutical group demonstrated improved postprandial glucose metabolism, including a 5% reduction in 2-h OGTT glucose and preservation of active GLP-1 levels. In contrast, the placebo group exhibited a decline in GLP-1 and increased insulin resistance. Supplementation also resulted in a 12% reduction in TNF-α, a 7.5% increase in plasma antioxidant capacity (FRAP), and modest but significant decreases in body weight, fat mass, and BMI (all p ≤ 0.05). Additionally, systolic blood pressure was reduced by 4%, potentially associated with improved antioxidant status and higher dietary potassium intake.ConclusionThese findings suggest that citrus flavonoids may serve as a safe and effective nutritional adjunct to metformin in the early management of prediabetes. Benefits include improved postprandial glycemia, maintenance of GLP-1 levels, reduced inflammation and oxidative stress, and modest improvements in body composition and blood pressure. Further long-term studies are warranted to confirm these outcomes and elucidate underlying mechanisms.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06005142.